STRATEGI PEMASARAN DALAM MENINGKATKANKEPUTUSAN PEMBELIAN KONSUMEN PADA DMCOFFEA NUSANTARA - Martines, Joelando Fatima C C; Prasojo, Eko; Arisman, Arisman; Fitriyana, Mifta (Program Studi Manajemen, 2022)
The purpose of this study is to find out how the marketing strategy is applied by Dm Coffea Nusantara in increasing consumer purchasing decisions. The population is a generalization area consisting of objects or subjects that have certain qualities and characteristics that are determined by researchers to be studied and then conclusions drawn. Meanwhile, this study examines marketing strategies in increasing purchasing decisions at Pamella One supermarkets. So that the object of this research is the person responsible for Dm Coffea Nusantara which consists of management. Based on the results of research conducted by researchers, it can be concluded that the success of the marketing mix of Dm Coffea Nusantara, namely the efforts made by Dm Coffea Nusantara in terms of providing the products provided, namely by maintaining product quality, from ingredients to the production process. With targets for all groups, Dm Coffea Nusantara must maintain the quality of its products so that consumers are not tempted by other batik products. DM Coffea Nusantara's efforts to set prices are according to the target market. Because this target applies to all people, so provide affordable prices with estimated expenses but by emphasizing costs on the products offered so that the prices that have been set even though they are cheap but still make a profit and can be used for business playback Dm Coffea Nusantara.